Individual condition, but not fledging phenology, carries over to affect post‐fledging survival in a Neotropical migratory songbird. (4th April 2019) - Evans, Dean R.; Hobson, Keith A.; Kusack, Jackson W.; Cadman, Michael D.; Falconer, C. Myles; Mitchell, Greg W.
Abstract : Migratory animals face severe time and energy constraints during their annual cycle. These constraints may be exacerbated in young animals by conditions experienced during development that can affect both phenotype and phenology. For young migratory songbirds, the period between fledging and autumn migration, the post‐fledging period, is believed to represent a time of intense selective pressure. However, there has yet to be a study that has assessed post‐fledging survival for the entirety of the post‐fledging period, probably due to the challenge of following juveniles as they move broadly across the landscape (tens to hundreds of kilometres). To overcome this challenge, we used an automated radiotelemetry array spanning 60 000 km 2 in southern Ontario, Canada, and miniature digital radiotelemetry tags to track 216 juvenile Barn Swallows Hirundo rustica continuously from fledging to migration. We hypothesized that young that fledged in better condition and earlier in the breeding season would have higher survival relative to birds fledging in poorer condition, because they have more energy to deal with resource constraints, and that early‐fledging birds would depart on migration earlier than late‐fledging birds because there is probably a fixed period of time required post‐fledging to prepare for migration. We found that average cumulative apparent survival was 42% and that condition in the nest was a strong positive predictor of post‐fledging apparent survival. We also found that birds that fledged earlier in the season departed on migration earlier in the autumn relative to late‐fledging birds. Contrary to our prediction, average apparent survival was equal for early‐ and late‐fledging birds. Our results suggest that factors during development that promote better nestling condition are critical for predicting future apparent survival prior to migration. Differences in annual apparent survival between early‐ and late‐fledging songbirds, as commonly observed, may be driven by events occurring at later stages of the annual cycle.